Giacomo Crosignani C. M., La teoría del naturale e del soprannaturale secondo S. Tommaso d'Aquino, Collegio Alberoni, Piacenza, 1974, 104 pp. - Mirás, Eduardo (1976)
Fil: Mirás, Eduardo. Investigador independiente